A SEMANTIC ANALYSIS ON ENTAILMENT FOUND IN THE MOVIE “MOANA” - Liza Muharina Bayazid (LINGUISTIK TERAPAN, 2023)
This research is under the scope of Semantics. The aims of this study are (1) to analysis the types of entailment and (2) to describe the orders of entailment found in the movie Moana (2016) and to describe the order of entailment applied in the movie Moana (2016). This research employed descriptive qualitative method. This research aimed at describing the language which is used in the movie Moana (2016). This research attempts to describe by using of proposed by Griffiths (2023) and Crouch (2003) theory as a theory of types of entailment found in the movie Moana (2016).  Therefore, the data of this research study is the transcription of the script movie Moana (2016). In this research, the form of the data was sentences in spoken language which is uttered in the movie. The sentences uttered can be in the context of dialogues with other characters or monologues. The results of the analysis showed from the total 20 data, one-way entailment type was found 8 times (40%), two-way entailment 5 times (25%), and metaphorical entailment 7 times (35%). Compared to another types of entailment, one-way entailment is most dominantly used of entailment. One-way entailment is on the highest rank since it is the most common entailment uttered by people. Two-way involvement can be seen in two or more sentences that have the exact same meaning. It was an idea that was said over and over again. In Moana's speech, every metaphorical implication consists of a metaphorical image and its meaning.